A SIMPLE SCHOOL PROFILE WEBSITE USING WORDPRESS AS AN INFORMATION AND PROMOTION MEDIA - Gardenia, Nia; Gusniwati, Mira; Rahadyan, Andri; Kurniawan, Indra (Universitas Muhammadiyah Mataram, 2021)
Abstract: A school profile website is a website that contains information about a school to introduce and provide the information to other parties such as the communities, parents, or partners of the school itself. This community service activity aims to raise awareness for school managers and teachers about the importance of using the internet/website to develop the potential of schools. The method of implementation is a workshop. There are 13 participants, who are teachers and staff in TK Qurrota A’yun and PAUD Mawar. The results in this community service activity are that around 20% of participants can create a simple school profile website using WordPress, and around 30% of participants can use the website as an information and promotion media.